2004
DOI: 10.1002/hyp.1473
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of bedload transport processes under unsteady flow conditions

Abstract: Abstract:Hydraulic engineering is usually based on theoretical analysis and/or numerical modelling simulation. As the dynamic behaviour of sediment movement under unsteady flow is still unclear, and field measurement is comparatively difficult during a large flood, prior investigations through flume experiments are required. A series of flume experiments, conducted using different inflow hydrographs without sediment supply from upstream, was carried out to investigate the sediment transport process under unste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
130
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(148 citation statements)
references
References 15 publications
13
130
3
Order By: Relevance
“…However, our knowledge on how matter, particularly sediment, is transported under unsteady flow conditions is still insufficient. This situation triggered a good deal of experimental, theoretical and computational efforts exploring how it works (Bombar, 2016;De Sutter et al, 2001;Julien et al, 2002;Lee et al, 2004;Mao, 2012;Mrokowska et al, 2016;Phillips and Sutherland, 1990;Wang et al, 2015). Nevertheless, the problem of bedload transport is still open for systematic research.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our knowledge on how matter, particularly sediment, is transported under unsteady flow conditions is still insufficient. This situation triggered a good deal of experimental, theoretical and computational efforts exploring how it works (Bombar, 2016;De Sutter et al, 2001;Julien et al, 2002;Lee et al, 2004;Mao, 2012;Mrokowska et al, 2016;Phillips and Sutherland, 1990;Wang et al, 2015). Nevertheless, the problem of bedload transport is still open for systematic research.…”
Section: Introductionmentioning
confidence: 99%
“…They varied in terms of various factors, such as the shape of unsteady flow hydrograph, e.g., triangular (Lee et al, 2004), trapezoidal (Bombar et al, 2011), step-wise (Mao, 2012), naturally shaped (Humphries et al, 2012); bed composition -uni-modal or bimodal (Wang et al, 2015); supply of sediment from upstream (Mao, 2012); initial bed conditions -armoured bed (Bombar et al, 2011) and not armoured bed (Humphries et al, 2012), or duration of flow from a few minutes (Guney et al, 2013) to a few hours (Mao, 2012). Some studies took into account or commented on scaling from natural to laboratory conditions, e.g., (Cooper and Tait, 2009;Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In reviewing different studies, it can be concluded that many researchers have used the following unsteady parameter: (Graf and Suszka 1985;Yen and Lee 1995;Song and Graf 1996;Nezu et al 1997;Lee et al 2004;Ahanger et al 2008;Bombar et al 2011): where u *b is the bed shear velocity associated with the steady base flow before hydrograph passages. It can be seen that flow unsteadiness increases with increasing parameter P. However, this parameter takes into account the duration of the hydrograph only and not the steepness of the rising limb of the hydrograph.…”
Section: Effective Parameters On Sediment Transport In Unsteady Flow mentioning
confidence: 99%
“…Lee et al (2004) introduced two other parameters which influence bed load transport during hydrograph events:…”
Section: Effective Parameters On Sediment Transport In Unsteady Flow mentioning
confidence: 99%
See 1 more Smart Citation